The effect of supplementation of Lactococcus lactis strain as probiotic on the growth and survival of Litopenaeus vannamei - Baharuddin, Nur Alya Syafiqah; Wan Abdul Ghani, Wan Alia; Che Omar, Siti Fairuz; Nawi, Mohd Firdaus; Tengku Abdul Hamid, Tengku Haziyamin (2023)
Introduction: Acute Hepatopancreatic Necrosis Disease (AHPND) or Early Mortality Syndrome (EMS) is a bacterial disease in shrimps caused by pathogen Vibrio parahaemolyticus. It has culminated in huge loss in global shrimp production due to mass mortality. A probiotic strain Lactococcus lactis strain FA1 was recently isolated from shark intestine, showing inhibition towards the growth of the pathogen. Due to inhibitory potential, the effect of probiotics strain on growth performance of shrimp infected with V. parahaemolyticus was evaluated. Methods: The probiotic strain was incorporated into feed for juvenile shrimps Litopanaeus vannamei for 3 weeks before which they were then challenged with pathogen Vibro parahaemolyticus. The study compares 4 shrimp groups: Control (Without any treatment); Group A (Probiotic treated, uninfected); Group B (Probiotic treated, infected) and Group C (No probiotic, infected). The survival and growth performance (weight and length gain) of shrimps were evaluated in the following 30 days. Statistical analyses (ANOVA; Post Hoc Tukey) were used to compare between shrimp groups. Results: In general, infected shrimp demonstrated some of the key symptoms of AHPND (pale or white hepatopancreas), transparent body and erratic swimming behaviour. The supplementation of probiotics resulted in a reduced mortality for infected shrimp. The probiotic treated shrimp group significantly (P value< 0.05) showed a better weight gain, compared to both infected and uninfected group. Meanwhile, some of the infected shrimps were able to show recovery from infection. Conclusions: This indicated that the strain Lactococcus lactis is highly suitable for use as the future probiotic in shrimp aquaculture.